Guideline for managing ectoparasitic infestations (scabies and pediculosis) in the context of pharmaceutical care - Silva Costa Gonçalves, Nicolas; de Tarso Silva, Saulo; de Oliveira Barbosa, Ana Paula; Paula de França, Francisco Alisson; Brandão Alves Silva, Fabiana; Pereira Calado, Gustavo; Fonseca Lima, Rodrigo; Marques dos Reis, Tiago; Santos Santana, Rafael (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To systematize, through evidence-based practice, the management of self-limiting cases of ectoparasitoses (scabies and pediculosis) within the context of Pharmaceutical Care. Methods: The ADAPTE method was adopted as a structured process for literature review and guideline development. Additionally, the tools Appraisal of Guidelines for Research & Evaluation – version II (AGREE II) and Grading of Recommendations Assessment, Development and Evaluation (GRADE) were used for the analysis of the selected practice guidelines and for the categorization of evidence, respectively. Results: Medical history taking is a fundamental step in the intervention strategy and in confirming the self-limiting nature of ectoparasitoses, enabling the analysis of the location and characteristics of the condition, as well as referral in cases of suspected secondary infections. Non-pharmacological interventions are limited to more traditional practices aimed at reducing infestation, such as mechanical removal methods for pediculosis and descontamination measures and health education for scabies. Regarding pharmacological measures, there are few available options, with benefits and limitations that vary according to the patient’s profile. As first-line treatment, topical formulations in the form of creams or lotions containing permethrin and oral ivermectin should be prioritized. The pharmacist must be alert to monitor warning signs that may require referral, such as sensitivity to medications, signs of infections with discharge, immunocompromised patients, and more frail elderly individuals, who are susceptible to the development of crusted scabies.